Factors Influencing Tax Aggressiveness in Manufacturing Companies in Indonesia: An Analysis of Corporate Social Responsibility, Leverage, and the Moderating Role of Good Corporate Governance - Yudhistira Ardana; Utama, Fikri Rizki; Lestari, Etty Puji (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
This research analyzes the factors influencing tax aggressiveness in manufacturing companies in Indonesia, focusing on Corporate Social Responsibility (CSR), leverage, and the moderating role of Good Corporate Governance (GCG). Tax aggressiveness refers to the efforts of companies to reduce their tax obligations, both legally and illegally. Data show that Indonesia's tax ratio has declined, reflecting the negative impact of tax aggressiveness on state revenue. This study employs a quantitative approach using panel data analysis of companies listed on the Indonesia Stock Exchange from 2020 to 2022. The findings indicate that CSR has a positive but not significant effect on tax aggressiveness. Leverage has a positive and significant effect, while liquidity also shows a positive impact on tax aggressiveness. On the other hand, independent commissioners moderated by CSR exhibit a negative but not significant influence. This study provides important insights for companies and regulators. Companies need to manage tax strategies ethically, and regulators should enhance oversight of tax aggressiveness practices. This research is expected to provide an empirical basis for better policymaking and encourage companies to use CSR as a tool to enhance tax compliance rather than disguise tax aggressiveness.